Successful teaching placement in Scotland primary and early years - Medwell, Jane, 1962-; Simpson, Frances (Frances Mary); Sage eBooks (Exeter : Learning Matters, 2008)
This title combines the information and support that students need to help them prepare for, enjoy and maximise the benefits of teaching placements for their professional development. It has been specifically written for the education system in Scotland.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Elementary school teaching -- Scotland; Elementary school teachers -- Employment -- Scotland; Electronic books